Comparison of cooperative learning through use of an immersive virtual reality anatomy model and a 3D plastic anatomical model - Shin-Yun Chen; Daniel Salcedo; Bu-Yuan Hsiao; Wen-Cheng Huang; Bor-Chyuan Su; Jiun-Lin Horng (BMC Medical Education)
Abstract Background Traditional anatomy education relies on lectures, visual aids, and cadaver dissections. However, limited cadaver availability often necessitates the use of plastic models to aid 3D understanding. Virtual reality (VR) presents an immersive alternative that may enhance spatial learning without requiring cadavers. Despite its potential, few studies have directly compared VR with traditional methods in anatomy education. Objective This study aimed to compare the learning outcomes of first-year anatomy students using either VR or plastic 3D models for anatomical instruction. Methods First-year anatomy students were divided into two groups: one using VR and the other using plastic models. They participated in weekly anatomy sessions consisting of 2-hour lectures followed by 2-hour laboratory sessions covering various anatomical systems. After the lectures, students engaged in laboratory activities using either plastic models or immersive virtual reality (iVR) for 3D spatial anatomy learning, with iVR participants capturing screenshots of assigned targets for verification. Each session concluded with an online image-based multiple-choice quiz to assess anatomical identification and understanding. Results Students from the Department of Nutrition and Health Sciences (NHS) and the Department of Medical Laboratory Science and Biotechnology (MLSB) at Taipei Medical University (TMU) participated in the study. Students in the VR group initially struggled due to the time required to adapt to the system, which was reflected in their significantly lower scores in week 2 for both NHS (80.35 ± 2.04 vs. 88.82 ± 1.64, p < 0.0019) and MLSB (72.23 ± 1.81 vs. 88.55 ± 1.67, p < 0.0001). However, in subsequent weeks, while iVR scores were slightly lower, the differences were not statistically significant, and by the later weeks, there was no significant difference in quiz performance between the two groups, with comparable scores observed in weeks 8 and 10 for NHS. Conclusions VR provides a viable alternative to plastic models for anatomy education. Although students require an adaptation period, their performance eventually matches that of students using traditional plastic models. This study is the first to quantitatively compare VR and plastic models in anatomy instruction.